Intravenous paracetamol infusion versus intramuscular tramadol as an intra-partum labor analgesic - Patil, Rashmi; Rayadurg, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We read with interest the article “Intravenous paracetamol infusion versus intramuscular tramadol as an intra-partum labor analgesic” by Mohan H et al published in November - December 2015, volume 4 issue 6 of International Journal of Reproduction, Contraception, Obstetrics and Gynecology.